Comparative studies of social and political elites - Gulbrandsen, Trygve (Elsevier JAI, 2006)
How can the existence of elites be compatible with democratic governance? Any democratic society is inevitably confronted by this basic question. This book reviews existing research on elites and their interactions with those around them. How the recruitment to elites changes in the long run according to class and gender is one of the core themes of the present volume. Other topics explored include the relationship between elites and the population, collective action and elite cohesion, and elites and democracy. The approach is multinational, with examples provided from countries around the world. This is a valuable book for social science students and researchers of many disciplines, including sociology, political science and psychology. It offers a review on historical and current research on elites in society and includes an extensive discussion of class and gender. Examples from countries in different parts of the world allow for international insights.
Keywords: Elite (Social sciences) -- Europe, Northern -- Cross-cultural studies.; Democracy -- Europe, Northern.; Elite (Social sciences) -- Europe -- Cross-cultural studies.; Democracy -- Europe.; Social groups.; Social Science -- Social Classes.; elektronické knihy; Electronic books.; electronic books